Surface structure of rubber leaf related to the interaction Phytophthora capsici - Hevea brasiliensis - Santos A F Dos; Alfenas A C; Maffia L A; Matsuoka K (Boletim de Pesquisa Florestal, 1999)
This study was aimed at elucidating the interaction between Phytophthora capsici and the rubber plant (Hevea brasiliensis). Histological studies were performed using light and electron microscopy (scanning and transmission). Germ tubes of the fungus show that penetration usually occurred through stomata, and rarely through epidermis at the abaxial leaf surface. Penetration through stomata was rare into the mature leaf. No stomata were found on the adaxial surface of young leaves, and here direct penetration into epidermal cells was common. No penetration was seen on the mature leaf, probably due to the thickness of the cuticle.
Source Year: 2000
Keywords: Hevea brasiliensis; Phytophthora capsici